Formas de deconstrucción social en la Ilíada: el enfado y la ira - Montes Miralles, M.ª Yolanda (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2007)
The exclusive social language that agathoi display in the Iliad includes a series of procedures/strategies aimed at the preservation of aristocratic kosmos and set those behaviours that deconstruct the above mentioned order. Among those, anger and wrath. The following pages deal with the analysis of some of the most noteworthy words and linguistic forms related to fury and those psycho-social contexts in which they appear. Sometimes any translation will be avoided, since the terms we are working on are cultural as well as symbolic.